2013
DOI: 10.3344/kjp.2013.26.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Vertebroplasty for the Subsequent Refracture of Procedured Vertebra

Abstract: Vertebroplasty (VP) can effectively treat pain and immobility caused by vertebral compression fracture. Because of complications such as extravasation of bone cement (polymethylmethacrylate, PMMA) and adjacent vertebral fractures, some practitioners prefer to inject a small volume of PMMA. In that case, however, insufficient augmentation or a subsequent refracture of the treated vertebrae can occur. A 65-year-old woman visited our clinic complaining of unrelieved severe low back and bilateral flank pain even a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…However, as with the three cases reported here, the cemented vertebrae can recollapse after PV 10 12 13 16 22 23. Regarding the risk factors for this complication, Kang et al 23 suggested that a higher preoperative local kyphotic angle and a higher sagittal index24 may result in refracture, based on a comparison of patients with or without refracture.…”
Section: Discussionsupporting
confidence: 57%
“…However, as with the three cases reported here, the cemented vertebrae can recollapse after PV 10 12 13 16 22 23. Regarding the risk factors for this complication, Kang et al 23 suggested that a higher preoperative local kyphotic angle and a higher sagittal index24 may result in refracture, based on a comparison of patients with or without refracture.…”
Section: Discussionsupporting
confidence: 57%
“…As the safety and efficacy of PVP were gradually recognized by spine surgeons, this treatment was widely used in clinical practice. Recently, an increasing number of cases with the recollapse of cemented vertebrae after PVP without additional trauma have been reported[ 21 , 22 ]. This recollapse is considered a further insufficiency fracture that results in more severe symptoms, deserving our attention.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of patients can develop disuse osteoporosis or become disabling and even fatal due to long-term bedridden, muscle atrophy and reduced weight-loading. Thus, scholars try to use surgical treatment for severe compression fracture [8,9] . But it is still controversial on the puncture path and bone cement injection.…”
Section: Discussionmentioning
confidence: 99%